Organic sensitizers with modified di(thiophen-2-yl)phenylamine donor units for dye-sensitized solar cells: a computational study - Namuangruk S. (2014)
A new series of organic donor-π-acceptor (D-π-A) dyes namely B1-6 with modification of donor groups by introducing thiophene (as D) and fluorene-connected carbazole on top of thiophene (as 2D-D) in phenylamine moieties, and with elongation of π-spacer unit of thiophene (1-3 units) in the π-spacer, were molecularly designed by using density functional theory (DFT) and time-dependent DFT. The nature of intramolecular charge transfer of all dyes was elucidated by means of frontier molecular orbital analysis, electronic structures, and absorption spectra to provide their potential use for dye-sensitized solar cells (DSSCs). The structural results show that the 2D-D-π-A dyes have a nonplanar structure on the D-D moiety that may suppress the aggregation of dye and yet maintain the conjugation in the whole D-π-A moiety. The systematically elongating π-spacer of B4-6 dyes with increasing number of thiophene group and the introducing 2D into D-π-A dyes give the redshift on absorption peak and broaden the absorption range, which are in excellent agreement with available experiment. Thus, this redshift improves their overall light-harvesting efficiency (LHE) better than the B1-3 dyes. Among the six dyes, B6 would have the best performance because it has the highest predicted LHE at the maximum absorption wavelength (λmax) and the suitable driving force ΔGinject of the electron injection from the excited state of dyes to the conduction band of TiO2. The prototype of DSSCs performance of selected dyes was further simulated using the chemisorption of dyes onto the (TiO2)38 cluster to reveal the nature of the electron injection mechanism. This current work is expected to assist in the molecular design of new metal-free organic dyes for use in DSSCs yielding highly efficient performance. © 2014 Springer-Verlag Berlin Heidelberg.